PTEN deletion in the adult dentate gyrus induces epilepsy - Jennifer M. Yonan; Kevin D. Chen; Tallie Z. Baram; Oswald Steward (Neurobiology of Disease, 2024)
Embryonic and early postnatal promotor-driven deletion of the phosphatase and tensin homolog (PTEN) gene results in neuronal hypertrophy, hyperexcitable circuitry and development of spontaneous seizures in adulthood. We previously documented that focal, vector-mediated PTEN deletion in mature granule cells of the adult dentate gyrus triggers dramatic growth of cell bodies, dendrites, and axons, similar to that seen with early postnatal PTEN deletion. Here, we assess the functional consequences of focal, adult PTEN deletion, focusing on its pro-epileptogenic potential. PTEN deletion was accomplished by injecting AAV-Cre either bilaterally or unilaterally into the dentate gyrus of double transgenic PTEN-floxed, ROSA-reporter mice. Hippocampal recording electrodes were implanted for continuous digital EEG with concurrent video recordings in the home cage. Electrographic seizures and epileptiform spikes were assessed manually by two investigators, and correlated with concurrent videos. Spontaneous electrographic and behavioral seizures appeared after focal PTEN deletion in adult dentate granule cells, commencing around 2 months post-AAV-Cre injection. Seizures occurred in the majority of mice with unilateral or bilateral PTEN deletion and led to death in several cases. PTEN-deletion provoked epilepsy was not associated with apparent hippocampal neuron death; supra-granular mossy fiber sprouting was observed in a few mice. In summary, focal, unilateral deletion of PTEN in the adult dentate gyrus suffices to provoke time-dependent emergence of a hyperexcitable circuit generating hippocampus-origin, generalizing spontaneous seizures, providing a novel model for studies of adult-onset epileptogenesis.